Competitiveness Model of Bioethanol Industry - Muzakar Isa; Kusmiati Kusmiati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2013)
The need for energy is increasing every year. More than 80% of energy needs met by fossil fuels derived from petroleum and natural gas. To anticipate, the Government issued Presidential Regulation No. 5 of 2006 on the national energy. In this regulation, the government took steps to saving energy and looking for new sources of energy that are renewable and environmentally friendly. One is bioethanol. This study aims to analyze the competitiveness of bioethanol industry in Bekonang Sukoharjo. This study used mixed methods, namely the incorporation of quantitative and qualitative methods in a single study. The measurement of competitiveness is using Porter's Diamond Model. The results show the competitiveness of bioethanol industry is influenced by business strategy, potential buyers, working capital and innovation. Currently, bioethanol industry competitiveness is low.